Just RM5,000 to hire hit man: Fees vary based on risks, rank and profile of victim - Ahmad, Razak; Ng, Si Hooi; Raman, A. (The Star, 2013)
CONTRACT killers are being hired for as low as RM5,000 by those who want to have their enemies bumped off, Harian Metro reported.